THU0324 Neutrophils in giant cell arteritis: monitoring disease progression during therapy tapering. (15th June 2017) - Kuret, T; Lakota, K; Žigon, P; Ogrič, M; Rotar, Ž; Ješe, R; Sodin-Šemrl, S; Čučnik, S; Tomšič, M; Hočevar, A
Abstract : Background: Giant Cell Arteritis (GCA) represents a medical emergency due to risk of permanent vision loss and/or cerebrovascular insults. Polymyalgia rheumatic (PMR) frequently coexists with GCA 1 . No diagnostic or prognostic markers are yet known for GCA and predicting relapses during steroid therapy tapering is difficult. Biomarkers, such as serum amyloid A (SAA) and interleukin-6 (IL-6) provide added value for monitoring inflammation and a recent investigational study indicated the potential use of neutrophils and their surface markers in GCA pathogenesis 2 . Objectives: To determine the percentage of neutrophils, T and B cells, and the mean fluorescence intensity (MFI) of L-selectin (CD62L) and integrin αM (CD11b) on CD16 + neutrophils in peripheral blood of newly diagnosed, untreated GCA and PMR patients vs. healthy controls (time 0) and at GCA follow-up (7, 30 and 90 days after therapy). Methods: Flow cytometry of stained, lysed and fixed whole blood 2 was performed in 10 GCA patients (6 followed longitudinally), 7 PMR patients and 5 healthy controls (7-colour immunophenotyping kit, Miltenyi). Levels of SAA and IL-6 were measured in sera of GCA patients (n=6) using nephelometry and ELISA, respectively. Results: Percentage of neutrophils was significantly higher at time 0 in GCA and PMR patients compared to healthy controls. Expression of both CD62L and CD11b on CD16 + neutrophils was also higher in GCA and PMR patients, as compared to healthy controls. Longitudinally, GCA patients showed an initial decrease in percentage of neutrophils at day 7 in comparison with time 0, increasing on days 30 and 90, while both T (CD4 + ) and B cells exhibited a significant elevation in % at day 7, with a decline at days 30 and 90. The MFI of neutrophil CD62L steadily decreased from day 0 (85.80±45.45) to day 7 (71.99±29.93) and day 30 (57.61±42.17), while showing a substantial increase on day 90 (88.54±60.35). CD11b expression diminished initially and remained reduced on day 90. Levels of SAA and IL-6 declined sharply from day 0 to 7 (>10-fold drop) and day 30, with gradual elevation of both on day 90. Conclusions: Neutrophil CD62L may represent a good surface marker for monitoring disease progression following glucocorticoid tapering. SAA and IL-6 exhibit a sharp decrease at early time points, increasing at day 90. In the future, a larger, longer study of neutrophils and their CD62L expression could support clinicians in their decision when and how to re-evaluate therapy in GCA patients. References: Schmidt J, Warrington KJ. Polymyalgia rheumatica and giant cell arteritis in older patients: diagnosis and pharmacological management. Drugs & aging. 2011;28651–66. Nadkarni S et al. Investigational analysis reveals a potential role for neutrophils in GCA disease progression. Circ.Res. 2014;114:242–48. Disclosure of Interest: None declared